Human papillomavirus infection and associated risk of preterm birth - Simona Daniela Savu (Popescu); Alina-Gabriela Marin; Daniel Codreanu; Radu Vladareanu (Romanian Journal of Infectious Diseases, 2022)
Introduction. The human papilloma virus (HPV) is a virus usually transmitted through mucocutaneous contact directly with the infected organs, resulting in a sexually transmitted infection that exposes particularly young women to a high risk of developing neoplasia of cervical, anogenital, respectively oropharyngeal origin if the virus persists for more than 1-2 years. Our study aimed to detect the correlation between HPV infection and spontaneous preterm labor. Materials and methods. We conducted an observational comparative case-control study in the Department of Neonatology/Obstetrics and Gynaecology of Elias Emergency University Hospital on women diagnosed with HPV infection to assess the risk of preterm labour associated with this infection. Results. The overall group of patients was divided into two groups (confirmed and unconfirmed (or negative) with HPV infection). We observed that, among positive patients, there was a higher incidence of patients infected with a single HPV strain (n=36), followed by patients infected with 2 strains (n=7). Our study revealed the fact that only 4 cases (22.2%) had a history of preterm birth, as opposed to 77.8% (14 cases) who had no associated preterm birth history in the case of HPV genotype 16 positive patients. The data obtained showed no statistical significance (p=0.977). Conclusions. Preterm birth remains one of the leading causes of perinatal mortality and lifetime morbidity worldwide. HPV is a frequently diagnosed viral infection, but clinical studies have observed mixed results regarding the association of HPV 16 and the risk of preterm birth.